A Survey on the Use of Mobile Applications for People who Are Visually Impaired. (July 2017) - Griffin-Shirley, Nora; Banda, Devender R.; Ajuwon, Paul M.; Cheon, Jongpil; Lee, Jaehoon; Park, Hye Ran; Lyngdoh, Sanpalei N.
Introduction: The literature indicates that few studies have been conducted with persons with visual impairments (that is, those who are blind or have low vision) concerning mobile application or "app" usage. The current study explores the use of mobile apps with this population globally. Methods: A total of 259 participants with visual impairments completed an online survey. Descriptive statistics and bivariate tests were used to examine associations between demographic characteristics and mobile app use. Results: The participants rated special apps as useful (95.4%) and accessible (91.1%) tools for individuals with visual impairments. More than 90% of the middle-aged adult group strongly agreed with the practicality of special apps, a significantly higher percentage than was observed in the young and old adult groups. In addition, the participants with low vision considered special apps less accessible than did those with blindness (p < .05). Discussion: Results show that persons with visual impairments frequently use apps specifically designed for them to accomplish daily activities. Furthermore, this population is satisfied with mobile apps and would like to see improvements and new apps. Implications for practitioners: Developers of apps for individuals with visual impairments need to refine and test the existing apps. Practitioners need to be knowledgeable about app usage so they can provide effective instruction to their students or clients. This study provides preliminary information regarding app usage among persons with visual impairments.